IMPLEMENTASI BIMBINGAN DAN KONSELING OLEH GURU DALAM MENUNJANG KURIKULUM 2013 - Sukmawati Sukmawati (UNIVERSITAS BENGKULU, 2015)
The general objective of the study is to describe the implementation of the 2013 curriculum for counseling teacher at Vocational High School number 1 Seluma regency. In thisstudy, researchers investigated and described the problem of curriculum implementation in 2013 for teachers counseling. In these activities involve many parties including principals and teachers counseling, student achievement and students assisted counseling. The conclusions of this study is that the implementation of the curriculum for teachers 2013 counseling performing well. Implementation can be seen from the planning, implementation and evaluation of the activities of guidance counseling in school.Keywords: implementation, curriculum 2013, counseling